Spatial Structuring of Cellulase Gene Abundance and Activity in Soil - Choi, Jinlyung; Bach, Elizabeth; Lee, Jaejin; Flater, Jared; Dooley, Shane; Howe, Adina; Hofmockel, Kirsten S. (Frontiers in Environmental Science, 2018)
Microbial mechanisms controlling cellulose degradation in soil habitats remains a critical knowledge gap in understanding and modeling terrestrial carbon-cycling. We investigated land management and soil micro-habitat influences on soil bacterial communities and distribution of cellulose-degrading enzyme genes in three bioenergy cropping systems (corn, prairie, and fertilized prairie). Within the soil, aggregates have been examined as potential micro- habitats with specific characteristics influencing resource partitioning and regulation and consequently studied soil aggregate fractions from the fertilized prairie system. Soil bacterial communities and carbon-cycling gene presence varied across land management and soil microhabitats. Examination of genes specifically involved in cellulose-degradation pathways showed high levels of redundancy across the bioenergy cropping systems, but medium macroaggregates (1000-2000 um) supported greater cellulose-degrading enzyme gene abundance than other aggregate fractions and whole soil. Despite similar bacterial diversity among fertilized prairie aggregates, functional potential within the medium aggregates were predominantly associated with Actinobacteria and Proteobacteria. These findings represent gentic potential only, and our previous work on the same samples found elevated cellulase exo-enzyme activity in microaggregates. These contrasting results emphasize the importance of measuring community, functional genes, and metabolic potentials in a coordinated manner. Together, these data indicate that location within the soil matrix matters. Overall, our results indicate that soil aggregate environments are hot-spots that select for organisms with functional attributes like cellulose degradation, and future work should further explore micro-environmental factors that affect realized C-cycling processes.